Indispensability of enhancing palliative care and rebuttal of utilitarian autonomy argument for euthanasia - Malik, Mohammad Manzoor (2013)

(untitled)
Patient autonomy has a vital role in making decisions in medical practice; this right of a patient is accepted by international conventions and medical codes. However, in regards to terminally ill patients, this right becomes very problematic in regards to end of life decisions. Utilitarian ethicists motivated by materialistic worldview and growing individualism have made moral arguments based on autonomy for the permissibility of active euthanasia. However, their arguments are not justifiable because of their inherent problems, on one side; and failing short of consensus because of non-materialistic worldviews and strong family values of the Eastern world, on the other side. Therefore, a thorough appraisal is made of the distinction of biological and biographical life and pro-euthanasia arguments: the best interest, golden rule, and autonomy. The distinction and the rest of the arguments in aggregation make a complete, autonomy argument for euthanasia. The study demonstrates that the distinction of biological and biographical life is inadequate due to: (1) reductive fallacy “oversimplification”;; (2) slippery slope;; and (3) inconsistency with the arguments for active euthanasia. Furthermore, the best interest and golden rule arguments are based on subjective moral judgments; therefore, the arguments fail the universalization test. The argument from autonomy fails because (1) unsoundness of civil rights claim, self-ownership, and right of self-determination for right to death; (2) fallacious analogy between suicide and euthanasia; (3) unjustifiable impingement of patient’s autonomy on physician’s autonomy;; and (4) confounded autonomy of the terminally ill patients. Therefore, patient autonomy argument for active euthanasia is both morally and legally problematic, and it falls short of consensus because of philosophical, legal, religious, and cultural reasons. The researcher argues that the solution of tackling terminally ill patients lies in enhancing palliative care. This conclusion is supported by various researches which demonstrate that mostly those patients have thoughts of suicide and euthanasia that suffer depression, despair, hopelessness, and are kept in isolation from their kith and kin; and their isolation amounts to a greater degree to their suicidal ideation.